Estudo térmico e de materiais de um compósito à base de gesso e EPS para construção de casas populares - Santos, Reginaldo Dias dos (2008)
A housing unit was built to study the thermal performance, and of material using a composite made of gypsum and EPS ground. We used two techniques of construction, using blocks, and filling on the spot. Two compositions of the composite were studied. The blocks were fixed using conventional mortar. In the technical of filling on the spot were used PET bottles up inside the walls to provide mechanical and thermal resistance. Compression tests were realized according to the ABNT standard of sealing bricks. It is going to be shown an analysis of the thermal comfort through the use of thermocouples placed on the walls of the building, internally and externally. The manufacturing viability of houses, using recyclable materials, through the use of composite materials proposed will be demonstrated. The constructive aspects showing the advantages and disadvantages of the technique used also will be broached. The block used presents structural functions and thermal insulating, is low cost and represents an alternative to the use of EPS and PET bottles which are materials that end up occupying much space in the landfills, giving than an ecologically correct use. The results of thermal analysis shows the thermal comfort provided by the composite by the obtainment of a difference between the internal and external surfaces of the walls more exposed to the sun around 7º C. The average temperature of the air inside the building, around 28.0 º C was below the zone of thermal comfort recommended for countries with hot weather